2000
DOI: 10.1034/j.1600-0463.2000.d01-42.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal and systemic antibody responses after peroral or intranasal immunization: Effects of conjugation to enterotoxin B subunits and/or of co‐administration with free toxin as adjuvant

Abstract: The mucosa-binding molecules cholera toxin (CT) from Vibrio cholerae and heat-labile enterotoxin (LT) from Escherichia coli have previously been used as mucosal adjuvants and carriers for many types of antigen. However, since these molecules are toxic and cannot be used in human vaccines, it is important to study whether their non-toxic mucosa-binding B subunits, CTB and LTB, can be used as alternative safe mucosal adjuvants and/or carrier molecules. We have as a model protein antigen used human gammaglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
0
27
1
Order By: Relevance
“…No humoral response was observed when mice were fed on seven consecutive days with plant-based HBsAg in a total dose of 1 lg (data not shown), which also suggests that multiple and high-dose antigen oral administration is conducive to tolerance rather than immunity. The importance of low dosage and extended timing for oral immunization could also be confirmed for CT-B or LT-B which, despite being soluble proteins and untypical mucosal antigens, are absorbed by M cells thanks to their ganglioside-binding properties and then elicit an immune response in the intestinal mucosa (Holmgren et al 1994;Rask et al 2000). Some boost effect was observed when CT-B was delivered as late as 40 days post priming (Arakawa et al 1998).…”
Section: Discussionmentioning
confidence: 92%
“…No humoral response was observed when mice were fed on seven consecutive days with plant-based HBsAg in a total dose of 1 lg (data not shown), which also suggests that multiple and high-dose antigen oral administration is conducive to tolerance rather than immunity. The importance of low dosage and extended timing for oral immunization could also be confirmed for CT-B or LT-B which, despite being soluble proteins and untypical mucosal antigens, are absorbed by M cells thanks to their ganglioside-binding properties and then elicit an immune response in the intestinal mucosa (Holmgren et al 1994;Rask et al 2000). Some boost effect was observed when CT-B was delivered as late as 40 days post priming (Arakawa et al 1998).…”
Section: Discussionmentioning
confidence: 92%
“…This possibility is currently under investigation. The CT-B conjugated to an Ag was recently shown to more effectively enhance Ag-specific immunity than did LT-B-Ag conjugates after oral administration (23). The mechanism underlying this difference in adjuvant activity is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have now shown that neither CT-B nor LT-B enhances immune responses to mucosally coadministered protein Ags (2,14,21,22). However, some reports have suggested that CT-B and LT-B display mucosal adjuvant activity when large doses are given with proteins by the nasal route (2,13,23,24) or when enterotoxin B subunits are directly conjugated to the Ag itself (2,23). Previous studies have shown that nCT as adjuvant elicits potent mucosal and systemic CD4…”
mentioning
confidence: 99%
“…This additive boosts short-term protection against V. cholerae infection (Clemens et al, 1989), acting as a potent mucosal immunogen and as an immunoadjuvant (Rask et al, 2000). The two major types of oral vaccines against cholera are the killed whole cell-based and the genetically attenuated live vaccines (Shin et al, 2011).…”
Section: Population and Individual Control Measuresmentioning
confidence: 99%